Danshen-Shanzha formula for the treatment of atherosclerosis: ethnopharmacological relevance, preparation methods, chemical constituents, pharmacokinetic properties, and pharmacological effects - Xu, Qiong; Yu, Zhe; Zhang, Meng; Feng, Tian; Song, Fan; Tang, Haifeng; Wang, Siwang; Li, Hua (Frontiers in Pharmacology, 2024)
Danshen-Shanzha Formula (DSF) is a well-known herbal combination comprising Radix Salvia miltiorrhiza (known as Danshen in Chinese) and Fructus Crataegi (known as Shanzha in Chinese), It has been documented to exhibit considerable benefits for promoting blood circulation and removing blood stasis, and was used extensively in the treatment of atherosclerotic cardiac and cerebral vascular diseases over decades. Despite several breakthroughs achieved in the basic research and clinical applications of DSF over the past decades, there is a lack of comprehensive reviews summarizing its features and research, which hinders further exploration and exploitation of this promising formula. This review aims to provide a comprehensive interpretation of DSF in terms of its ethnopharmacological relevance, preparation methods, chemical constituents, pharmacokinetic properties and pharmacological effects. The related information on Danshen, Shanzha, and DSF was obtained from internationally recognized online scientific databases, including Web of Science, PubMed, Google Scholar, China National Knowledge Infrastructure, Baidu Scholar, ScienceDirect, ACS Publications, Wiley Online Library, Wan Fang Database as well as Flora of China. Data were also gathered from documentations, printed works and classics, such as the Chinese Pharmacopoeia, Chinese herbal classics, etc. Three essential avenues for future studies were put forward as follows: (a) develop and unify the standard preparation method of DSF as to achieve optimized pharmacological properties. (b) elucidate the functional mechanisms as well as the rationality and rule for the compatibility art of DSF by focusing on the clinic syndromes together with the subsequent development of preclinic study system in vitro and in vivo with consistent pathological features, pharmacokinetical behaviour and biomarkers. (c) perform more extensive clinical studies towards the advancement of mechanism-based on evidence-based medicine on the safety application of DSF. This review will provide substantial data support and broader perspective for further research on the renowned formula.